KREATIVITAS NURYANTO DALAM PENCIPTAAN DRAMATARI RAMAYANA - Putri Pramesti Wigaringtyas (Gelar : Jurnal Seni Budaya, 2014)
The article an effort to browse and convey the creativity problem of Nuryanto in creating the Dramatari (dancedrama) Ramayana. It conveys every factor that makes Ramayana interesting so that it becomes the inspirationof various forms of performing arts. It also conveys how the adaptation process of Nuryanto towards Ramayanastory that it becomes a genre of dance drama performing art. The research also describes analytically thecreative process of the creation. The method used is qualitative with historical approach of performing artsand sociology. Ramayana by Nuryanto is created in 1998 started from the concept of dance drama. In pouringhis work, Nuryanto bases on the idioms of Surakarta traditional dance treated by new pattern of treatmentwith double casting concept, multi characters, as well as creative and innovative. The minimalist costumeand the different structure of presentation have made the work strongly exist in every performance. DramatariRamayana by Nuryanto is really an interesting work for it always presents a different treatment and differentcreativity process in every performance since 1998.Key words: Ramayana dance drama, tradition, creativity, genre